Utilization of Coconut into Virgin Coconut Oil (VCO) to Improve the Economy of the Residents of Kalibatur Village, Tulungagung - Widati, Alfa Akustia; Zakki Fahmi, Mochamad; Nanik Siti Aminah; Budi Prasetyo, Antonius; Adiarto, Tokok; Rico Ramadhan (ANDAN JEJAMA: Indonesian Journal of Community Engagement (IJCE), 2025)
The coastal community of Sine Beach, Kalibatur Village, Tulungagung, Indonesia, has long thrived on fishing activities. In response to this, a community development service explores the alternative utilization of coconut, particularly the production of Virgin Coconut Oil (VCO), as a means of economic diversification. By integrating scientific principles with local traditions, the community learned to extract VCO and create various coconut-based products. This initiative not only broadened economic horizons but also fostered environmental sustainability. The programs aims to give economic impact to residents in Pantai Sine Tulungagung.